Developing a comprehensive model of hazard preparedness: Lessons from the Christchurch earthquake. (December 2015) - Paton, Douglas; Anderson, Ella; Becker, Julia; Petersen, Jessica
Abstract: Large, damaging earthquakes are rare. When they occur, they do so without warning. This makes being prepared for such occurrences important. However, the rarity of the events makes it difficult for people to fully understand the hazard consequences they need to be prepared for. Taking the view that the goal of preparedness is increasing people's ability to cope with and adapt to the demands and challenges encountered in disaster response and recovery periods, this paper examines the validity of conceptualizations of preparedness by identifying what people undergoing disaster recovery identified as essential for effective community response and recovery. Data on the latter were obtained from residents from five suburbs that experienced extensive physical damage and social and economic disruption (the "affected" group) by the 2011 earthquake identified as being required to be comprehensively prepared for future earthquakes. It then compares this with a sample from communities surrounding Christchurch that did not experience direct physical losses (the "unaffected group") from the earthquake to assess if they endorsed these categories. Identification of the similarities and differences in both the functional categories endorsed by each group and the respective predictors of each functional category is used to frame discussion of how analysis of earthquake response and recovery experience can inform the development of comprehensive preparedness programs. The paper concludes with a discussion of the implications of this for disaster risk reduction strategies based on previous earthquake events for countries that face high levels of seismic risk.